1999
DOI: 10.1016/s0895-7061(98)00261-1
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of resting blood pressure and heart rate in a sedentary population The heritage family study

Abstract: The familial aggregation of resting systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) was assessed in 98 white families, who participated in the HERITAGE Family Study, and were selected to be sedentary, and primarily nonobese and normotensive. In the present study, 522 family members were sedentary at baseline examination, and resting SBP, DBP, and HR measured during this examination were investigated. If physical activity level is a potent environmental factor, then we expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 19 publications
3
34
2
2
Order By: Relevance
“…In previous population studies, sibsib blood pressure correlations have been in the range of 0.14 to 0.18. 3 Similarly, in this black group of hypertensive individuals, sib-sib correlations for systolic and diastolic blood pressures, off of antihypertensive drug therapy, were generally within this range, even when these measurements were obtained at an inpatient clinical research center under standardized conditions. Compared with measurements at 1 point in time, higher heritability estimates were generally observed when multiple blood pressure measurements obtained over 24 hours were averaged.…”
Section: Kotchen Et Al Candidate Hypertension-related Phenotypesmentioning
confidence: 67%
See 1 more Smart Citation
“…In previous population studies, sibsib blood pressure correlations have been in the range of 0.14 to 0.18. 3 Similarly, in this black group of hypertensive individuals, sib-sib correlations for systolic and diastolic blood pressures, off of antihypertensive drug therapy, were generally within this range, even when these measurements were obtained at an inpatient clinical research center under standardized conditions. Compared with measurements at 1 point in time, higher heritability estimates were generally observed when multiple blood pressure measurements obtained over 24 hours were averaged.…”
Section: Kotchen Et Al Candidate Hypertension-related Phenotypesmentioning
confidence: 67%
“…[1][2][3] Estimates of the heritability of resting systolic and diastolic blood pressures, based on family studies, are generally in the range of 15% to 35%. In twin studies, heritability estimates of blood pressure are Ϸ60% for males and Ϸ30% to 40% for females.…”
mentioning
confidence: 99%
“…Blood pressure. A random-zero sphygmomanometer was used to determine resting blood pressure using the Heritage protocol (17). Readings were taken in the morning before 11:00 A.M. in a room with temperatures between 21 and 25°C.…”
Section: Interventionmentioning
confidence: 99%
“…These factors may act in an additive or multiplicative manner. Epidemiological studies have demonstrated that hypertension segregates within families 7 and its prevalence differs between ethnicities. 8 Common variants in a number of genes are thought to explain some of this difference.…”
mentioning
confidence: 99%